On the Importance, Origin, and Distribution of the Oat Plant - Ma’muraxon, Atabayeva; o’gli, Usmanov BahromDavronbek (American Journal of Biology and Natural Sciences, 2024)
Oats are considered to be the oldest crop, and in the wild they have been found since ancient times in a mixture with wheat and barley. Oat grain contains on average 13.3% protein, 4.7% oil, 40.1% starch, 13.2% tissue, 4.0% ash and 11.0% water. The amount of protein varies depending on the geographic region and high humidity. Cereals mainly contain B vitamins. Vitamin B1 (thiamine) - 4.5-8.0 mg / kg. All types of cereals and flour are made from oats.